Exploration of Urban Rail Transit Logistics Organization Models - LEI Xiaoyu; QIN Qing; SUN Xijing (Chengshi guidao jiaotong yanjiu)
Objective In order to make full use of the surplus capacity of urban rail transit and develop logistics services, with Shenzhen Metro as an example and based on the compatibility between urban distribution market and urban rail transit, the application models suitable for rail logistics are studied. Method Combined with the spatio-temporal matching relationship between supply and demand and the characteristics of urban rail transit, application scenarios that can be widely applied are proposed. Based on different modes of transportation, a study focusing on multiple logistics organization modes of urban rail transit is conducted. The rail logistics organization modes are explored and studied based on the express delivery scenarios. From the perspective of specific practice and transportation organization research, the organization modes, some problems and solutions of urban rail transit connecting with intra-city logistics, air logistics, high-speed rail logistics, and trunk land logistics are analyzed. The advantages and disadvantages of different transportation organization forms under different connection modes are analyzed. The timeliness and feasibility of the intra-city relay mode are verified through practical testing, and exploration experiences such as the logistics organization models for large hubs are proposed. Result & Conclusion Through research and practice, it has been found that: firstly, urban rail transit has the advantage of high timeliness in undertaking intra-city express delivery relay services in certain scenarios, and it proves the feasibility of the overall logistics organization. Secondly, in the design of high-speed urban rail transit hubs, the interconnection and interoperability of logistics functions should be fully considered, in order to achieve the trunk-to-node connection and transfer conditions for goods. Thirdly, the integration of the secondary express distribution center and the track yard can efficiently realize trunk land transportation connection, optimize and solve the last mile issues.